Microfluidic plug steering using surface acoustic waves. Issue 14 (16th June 2015) - Sesen, Muhsincan; Alan, Tuncay; Neild, Adrian
Abstract : A microfluidic chip capable of steering and unevenly splitting plugs at a Y-junction uses surface acoustic waves. Abstract : Digital microfluidic systems, in which isolated droplets are dispersed in a carrier medium, offer a method to study biological assays and chemical reactions highly efficiently. However, it's challenging to manipulate these droplets in closed microchannel devices. Here, we present a method to selectively steer plugs (droplets with diameters larger than the channel's width) at a specially designed Y-junction within a microfluidic chip. The method makes use of surface acoustic waves (SAWs) impinging on a multiphase interface in which an acoustic contrast is present. As a result, the liquid–liquid interface is subjected to acoustic radiation forces. These forces are exploited to steer plugs into selected branches of the Y-junction. Furthermore, the input power can be finely tuned to split a plug into two uneven plugs. The steering of plugs as a whole, based on plug volume and velocity is thoroughly characterized. The results indicate that there is a threshold plug volume after which the steering requires elevated electrical energy input. This plug steering method can easily be integrated to existing lab-on-a-chip devices and it offers a robust and active plug manipulation technique in closed microchannels.